2009
DOI: 10.1002/cbm.749
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of criminal thinking styles among civil psychiatric patients

Abstract: Independent samples t-tests revealed that five PICTS thinking styles were significantly higher in the psychiatric sample compared with the comparison sample of criminal offenders. Bivariate correlations revealed that the PICTS proactive composite scale was significantly related to and predicted by substance abuse and arrest history. CONCLUSIONS/CLINICAL IMPLICATIONS: Thinking styles which are typically associated with criminality were found in this sample of civil psychiatric patients. Cognitive remediation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
(40 reference statements)
0
24
0
Order By: Relevance
“…Furthermore, criminal thinking has been shown to partially mediate the relationship between mental illness and institutional violence for incarcerated PMI. 20 Notably, meta-analytic studies have found that, with regard to violent offending, criminal As previously noted, criminal thinking appears to be a general risk factor for crime committed by PMI, 18,19,24 but may also contribute to an explanation of violence. Specifically, inmates with severe mental illness (ie, schizophrenia or bipolar disorder), which are typically perceived to be more violent due to the presence of active symptoms, 25 displayed higher levels of criminal thinking than those without mental illness and those with less severe mental illness (ie, depression, posttraumatic stress disorder, and anxiety).…”
Section: Persons With Mental Illness Violence and Criminal Behaviormentioning
confidence: 87%
“…Furthermore, criminal thinking has been shown to partially mediate the relationship between mental illness and institutional violence for incarcerated PMI. 20 Notably, meta-analytic studies have found that, with regard to violent offending, criminal As previously noted, criminal thinking appears to be a general risk factor for crime committed by PMI, 18,19,24 but may also contribute to an explanation of violence. Specifically, inmates with severe mental illness (ie, schizophrenia or bipolar disorder), which are typically perceived to be more violent due to the presence of active symptoms, 25 displayed higher levels of criminal thinking than those without mental illness and those with less severe mental illness (ie, depression, posttraumatic stress disorder, and anxiety).…”
Section: Persons With Mental Illness Violence and Criminal Behaviormentioning
confidence: 87%
“…The high rate of substance use disorders and personality disorders may in part explain this difference, because these factors have been shown to correlate strongly with criminality (Sigurdson & Gudjonsson, ; Grann et al, ). Crime rates among people with mental illness are influenced by various factors such as arrest bias, inadequate treatment, acute symptoms of psychiatric illness (Hodgins & Janson, ) and psychological factors associated with criminality (Carr et al, ). Our findings are similar to previously reported effects of age and gender on imprisonment rate, with lower rate of imprisonment among older individuals and women (Steffensmeier & Motivans, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additional factors that have received less clinical attention are the antisocial factors, including antisocial associates, personality traits and cognitions (Lamberti 2007); despite the fact some antisocial thinking, such as externalization, rationalization and entitlement may be more prevalent among the mentally ill offending population than among general offenders (Carr et al 2009). …”
Section: Criminalization: Not Whether Rather Whymentioning
confidence: 98%